Commerce with a bit of ethics or ethics with a bit of commerce? The conundrum of British consumer co-operation 1863-1990. Issue 3 (17th July 2020) - Webster, Anthony; Wilson, John F.; Wong, Nicholas D.
Abstract : Purpose: This paper is concerned with the historical record of one business in the UK, which has long laid claim to the moral high ground in the conduct of its affairs – the amalgam of consumer co-operative business organisations, which eventually merged to become the Co-operative Group at the beginning of the 21st century. This paper aims to offer an assessment of the record of the British consumer co-operative movement's efforts to abide by and promote its values and principles during the first 137 years of its existence (1863 to 1990). Design/methodology/approach: The paper is developed using largely qualitative research methods and a variety of sources. These include archival resources and business-historical materials such as committee minutes and correspondence. These materials have been complemented by several semi-structured recorded interviews with senior members of the Co-operative Group. Findings: The authors develop several conclusions. First, where ethical choices were possible and no serious commercial interests were impaired, the co-operative movement could and usually did do its best to adhere to its principles. Second, in several instances, commercial interests did frequently trump ideals. Finally, the organisational structure of the movement made it very difficult to ensure that co-operative principles and values were adhered to. Originality/value: This paper presents a unique case-study that examines the inherent tension between commerce and ethics in the co-operative movement.